Educational psychology for the effective management of medical-psycho-pedagogical centres: a correlation study - A. Kasmi; B. Touri (Образование и наука)
Introduction. Educational psychology focuses on the psychological aspects of learning and teaching to optimise education by understanding how individuals develop skills and acquire knowledge in an educational context. Aim. The study aims to understand how educational psychology can help the effective management of medical-psycho-pedagogical centres (CMPPs) and to identify the links and synergies between the principles of educational psychology and the practice of managerial aspects within such centres. Research methodology and methods. The authors used a quantitative methodology based on a non-experimental correlational study. The sample included 100 CMPPs in the Ile-de-France region. The directors of these centres were invited to complete the questionnaire hosted on the Google Forms platform. The results were processed using IBM SPSS 29. Results and scientific novelty. Of the six relationships studied, the results revealed four significant relationships between the “psychology of education” variable and managerial aspects, namely team structure and management, quality and safety of care, patient data management and interprofessional cooperation. The above-mentioned relationships represent 80% of the significant relationships between educational psychology and managerial aspects. The scientific novelty of the research lies in examining the relationship between educational psychology and managerial dimensions, providing a clear vision of the essential role of educational psychology in the management of CMPPs. Practical significance. These results underline the importance for each country of integrating the principles of educational psychology into the development of their CMPPs. This is particularly crucial for Morocco, in alignment with the 2015–2030 strategic vision to establish these centres.